Bio-economic modelling for marine spatial planning application in North Sea shrimp and flatfish fisheries. (December 2015) - Bartelings, H.; Hamon, K.G.; Berkenhagen, J.; Buisman, F.C.
Abstract: Marine activities have been increasingly competing for space and reducing areas for fishing. The use of spatially explicit tools can assist the decision making process on defining the optimal location of closures for fishing due to these emerging activities. This paper presents the Spatial Integrated bio-economic Model for FISHeries (SIMFISH). In this model fishers behaviour is simulated based on optimal effort allocation. The added value of this model compared to other existing spatial management tools lies in the presence of (i) short and long term fishers behaviour (ii) spatial explicit stock and fleet dynamics and (iii) relatively low data requirements. As an illustration, SIMFISH is applied in this paper to estimate the impact of area closures in the North Sea. Overall area closures have a negative impact on the profitability of the fleets. This would be worsened with higher fuel prices and decreased stock productivity. Highlights: We present a spatial explicit bio-economic model to assess impact of area closure on fisheries. The model was applied in a case study to analyse how area closures in the North Sea impact shrimp and flatfish fisheries. The possibility of fleets to go fishing in other areas play a major role in determining the impact of area closures. This fleet flexibility is majorly impacted by higher fuel prices and stock productivity.